Production of cheap hand sanitizer with herbal ingredients. Issue 1 (February 2021) - Chakraborty, A; Mukhopadhyay, A; Sur, A; Ghosh, Dr. S
Abstract: Novel Corona Virus has spread to 188 countries around the world which made the people infected, facing moderate respiratory illness. Currently one of the major strategies to deal with COVID-19 and reduce community transmission of infections is the frequent use of hand sanitizers. However, a large section of common mass is unable to buy them due to higher price. Therefore, an approach has been presented here to produce cheaper sanitizers with easily available herbal ingredients like Aloe Vera gel, boiled water, surgical spirit, Glycerine etc. The estimated making cost of 100 ml of sanitizer was 16 rupees. The mass production of this sanitizer can be very effective for large scale use of sanitizers by common people.